Education of blind and visually impaired children of North America and the Caribbean - Orlansky, M. D.
This report provides an overview of recent population figures, types of educational programmes, and current issues concerning education of blind and visually impaired students in the United States, Canada, and the Caribbean
Keywords: Education of the blind